Overcoming immune checkpoint inhibitor-mediated T-cell exhaustion with a TCR β chain-directed selective dual T-cell activator - Shantel Angstadt; Lucas A. Horn; Kristen Fousek; Nika Rajabian; Haiyan Qin; Miriam M. Medina-Enriquez; Marcus D. Kelly; Nicole Hsiao-Sanchez; Thomas J. Meyer; Jacques Moisan; Madan Katragadda; Andrew Bayliffe; et al. (Journal of Experimental & Clinical Cancer Research, 2026)
Abstract Background Resistance to immune checkpoint inhibition (ICI) using antibodies against the PD-1/PD-L1 axis remains a significant clinical challenge. Here, we report that combination of anti-PD-1 with a bifunctional fusion molecule, anti-TCRβ-IL-2, comprised of a monovalent Fab that binds and activates the T-cell receptor (TCR) through distinct variable beta (Vβ) chain residues and an IL-2 molecule, mediates robust anti-tumor control in the context of ICI resistance. Methods Syngeneic murine models with varying levels of ICI-resistance were used to assess sensitization to ICI in combination with the anti-TCRβ-IL-2 therapy. Mechanisms of the combination therapy’s benefit were investigated by profiling tumor-infiltrating lymphocytes via flow cytometric, single cell transcriptomic, and histological analyses. Immune response efficacy and diversification was identified by the generation of multifunctional, tumor-associated antigen-specific and neoantigen-specific T-cell responses post-therapy. Results Unlike anti-PD-1 therapy alone that resulted in expansion of terminally exhausted CD8 + T cells and lack of anti-tumor effect, administration of anti-TCRβ-IL-2 followed by anti-PD-1 greatly enhanced anti-tumor efficacy leading to tumor cures and long-term protection in several murine models resistant to ICI. Analysis of tumor-infiltrating lymphocytes showed increased proliferation and markers of cytotoxicity in CD8 + and CD4 + T cells, reduced CD8 + T-cell exhaustion, and decreased proportion of regulatory CD4 + T cells in tumors of mice receiving TCRβ-IL-2 followed by anti-PD-1. Diversification of the immune response with increased number of multifunctional, neoantigen-specific T cells was observed in mice receiving anti-TCRβ-IL-2 followed by anti-PD-1, compared to each of the monotherapies. Conclusions A novel T-cell activation mechanism sensitizes refractory tumors to ICI via T-cell function revival and epitope spreading. From these results, a clinical trial is planned to evaluate the combination of an anti-TCRβ-IL-2 agent (invikafusp alfa) and anti-PD-1 in ICI-refractory non-small cell lung and castration-resistant metastatic prostate cancers.